Generation Unbound : Drifting into Sex and Parenthood without Marriage - Sawhill, Isabel V. (Book collections on Project MUSE., 2014)
Over half of all births to young adults in the United States now occur outside of marriage, and many are unplanned. The result is increased poverty and inequality for children. The left argues for more social support for unmarried parents; the right argues for a return totraditional marriage. In Generation Unbound, Isabel V. Sawhill offers a third approach: change ""drifters"" into ""planners."" In a well-written and accessible survey of the impact of family structure on child well-being, Sawhill contrasts ""planners, "" who are delaying parenthood until after they marry, with ""drifters, "" who